2016
DOI: 10.2147/amep.s107304
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of final-year medical students towards the impact of gender on their training and future practice

Abstract: IntroductionFollowing policy implementations to redress previous racial and gender discrepancies, this study explored how gender impacted on the clinical experiences of final-year medical students during their undergraduate training. It also gathered their perceptions and expectations for the future.MethodsThis cross-sectional, mixed-method study used a purposive sampling method to collect data from the participants (n=94). Each respondent was interviewed by two members of the research team. The quantitative d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 25 publications
1
18
1
Order By: Relevance
“…What is particularly noteworthy, however, is that we found that our gender, and status as a medical student, was the biggest contributor to a female patient’s reluctance to having a male student examine them, especially during our OBG rotation. This is in contrast to the study’s findings that the male student’s age was a greater influence than their gender on a patient’s decision 1. This difference from our experience may be due to cultural beliefs held in countries like South Africa, where this study was conducted, in comparison to the UK.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…What is particularly noteworthy, however, is that we found that our gender, and status as a medical student, was the biggest contributor to a female patient’s reluctance to having a male student examine them, especially during our OBG rotation. This is in contrast to the study’s findings that the male student’s age was a greater influence than their gender on a patient’s decision 1. This difference from our experience may be due to cultural beliefs held in countries like South Africa, where this study was conducted, in comparison to the UK.…”
contrasting
confidence: 99%
“…We agree with the findings of the study that there are obstacles to males performing intimate examinations, and even consultations, on female patients 1. This especially holds true in a multicultural city like London, where many different social, religious, and cultural beliefs exist.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…This so-called 'feminization' of the medical profession has been well documented in the UK, Europe and North America, where females account for more than 50% of medical school intakes and practicing physicians (Paik 2000;Searle 2001;Sibbald 2002;Van der Reis 2004;Levinson and Lurie 2004;Reichenbach and Brown 2004;Allen 2005;Heru 2005;Kilminster et al 2007;Dacre 2008;McKinstry 2008;Riska 2008;Drinkwater et al 2008;Maiorova et al 2008;Phillips and Austin 2009;Babaria et al 2009;Weizblit et al 2009;Roskovensky et al 2012;Bleakley 2013;Mudaly and van Wyk 2015;Van Wyk et al 2016). Although much less has been reported in developing countries, this trend appears similar (Al-Jarallah and Moussa 2003; National Association of Universities and Higher Education Institutions (ANUIES); Wildschut 2006, 2008;Mudaly and van Wyk 2015;Van Wyk et al 2016). In Kuwait, for example, female medical post-graduates have outnumbered males since 1993 (Al-Jarallah and Moussa 2003) and in Mexico since 1999 (National Association of Universities and Higher Education Institutions ANUIES).…”
Section: Introductionmentioning
confidence: 99%
“…The implication of this increased female medical workforce has been widely discussed (Searle 2001;Levinson and Lurie 2004;Allen 2005;Heru 2005;Kilminster et al 2007;Riska 2008;Riska and Novelskaite 2008;Dacre 2008;McKinstry 2008;Maiorova et al 2008;Weizblit et al 2009;Mudaly and van Wyk 2015;Van Wyk et al 2016). Riska (2008) contends that using the term 'feminization' to describe an increasingly female medical workforce embodies "predictions about qualitative changes in the practice of medicine" (p. 3).…”
Section: Introductionmentioning
confidence: 99%